Modelling an electrically turbocharged engine and predicting the performance under steady-state engine - K. Subramaniam, K. Subramaniam; Wan Salim, W. S. I. (Universiti Malaysia Pahang, 2021)
This paper discusses the evaluation of the energy recovery potential of turboshaft separated (decoupled) electric turbocharger and its boosting capability in a spark-ignition engine through simulation-based work and comparing it to a conventional turbocharged engine in terms of fuel consumption. The main objective of this study is to evaluate the amount of energy that can be recovered over a steady state full-load operating conditions and boosting capabilities from a decoupled electric turbocharger of an SI engine using a 1-D engine simulation software. The electric turbocharged system includes two motors and a battery pack to store the recovered electrical energy. Gt-Power engine simulation software was used to model both engines and utilizes each of the components described earlier. The conventional turbocharged engine is first simulated to obtain its performance characteristics. An electric turbocharger is then modelled by separating the turbine from the compressor. The turbine is connected to the generator and battery, whereas the compressor is connected to the motor. This electrically turbocharged engine was modelled at full load and controlled to produce the same brake power (kW) and brake torque (Nm) properties as the similarly sized conventional turbocharged engine. This step was necessary to investigate the effect an electrical turbocharger without a wastegate has on the engine’s BSFC and determine the energy that can be recovered by the electrical boosting components, and cycleaveraged fuel consumption was evaluated. The evaluation of energy recovered from the electrically turbocharged engine from the analysis can assessed in full-load steady state conditions that can be useful for research in part-load and transient studies involving the decoupled electrical turbocharger. The study revealed that a maximum of 21.6 kW of electrical power can be recovered from the decoupled electrical turbocharger system, whereas 2.6% increase in fuel consumption can be observed at 5000 rpm engine speed.